Where Tools Are Few: Constructing Limited-Word Bilingual Learner’s Dictionaries in a Low-Resourced Community in Malawi - Dicks, Ian David (Lexikos, 2025)
Many minority language communities in sub-Saharan Africa are required to navigate national education systems dominated by languages in which they are not largely proficient, and which they lack resources and tools to learn. When taken together with a low political will for resourcing minority languages, these become formidable barriers for learning and development (Matiki 2006: 244, 246; Prinsloo 2017: 20). Many minority languages are also not understood or spoken outside of these communities, and there are few resources to assist people to gain capacity in them, which results in large communication gaps. This paper examines how a team of non-professional Yawo lexicographers in Malawi worked to overcome these barriers in order to produce two limited-word bilingual learner’s dictionaries (English–Ciyawo; Ciyawo–English) in book and smartphone application forms. More specifically, it explains how the team was trained, the development of a limited organic corpus from oral interviews as a method for supplementing an unbalanced corpus, and the importance of collaboration. The paper also articulates the linguistic and pedagogical theories that are foundational to the project, including that second-language learners develop second-language competence more efficiently through engaging with a curated headword list of high-frequency and high-relevance words (Nation 2022: 15-17; Bayetto 2018: 12). Keywords: Ciyawo, poverty, bilingual, learner, dictionary, education, Malawi, Africa, Oxford, lexicography, smartphone, application, corpus, language